Research Progress on Coffee Biomass Material Capacitors - Kan, Xurundong; Pu, Jingwei; Liu, Yaning; Qiu, Li (International Journal of Public Health and Medical Research, 2026)
The increasing demand for sustainable energy storage solutions has driven research into eco-friendly materials, with coffee biomass emerging as a promising candidate due to its natural abundance and renewable characteristics. This review systematically examines the fundamental properties of coffee biomass-derived materials, highlighting their unique structural and chemical features that contribute to enhanced electrochemical performance. The application of these materials in capacitors demonstrates significant improvements in capacitance and cycling stability, attributed to their porous architecture and favorable surface chemistry. Furthermore, the integration of coffee-based components in energy storage devices showcases notable advancements in efficiency and environmental compatibility. The findings underscore the potential of coffee biomass as a viable alternative to conventional materials, offering both economic and ecological benefits. Future research directions emphasize the optimization of processing techniques and the exploration of hybrid systems to further elevate performance metrics, paving the way for broader implementation in next-generation energy technologies.